2017
DOI: 10.1373/clinchem.2016.261644
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin T: Smaller Molecules in Patients with End-Stage Renal Disease than after Onset of Acute Myocardial Infarction

Abstract: We found that cTnT forms in ESRD patients are small (<18 kDa) and different from forms seen in AMI patients. These insights may prove useful for development of a more specific cTnT immunoassay, especially for the acute and diagnostic phase of myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 29 publications
5
36
0
1
Order By: Relevance
“…Indeed, after myocardial infarction, cTnT and cTnI have been observed as free cTnT and cTnI, larger cTnT-I-C (77 kDa) and cTnI-C (40 kDa) complexes, and fragments (27)(28)(29)(30)(31). In contrast, in renal failure, cTnT circulates primarily as fragments (32 ), whereas the circulating form of cTnI in renal failure is unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, after myocardial infarction, cTnT and cTnI have been observed as free cTnT and cTnI, larger cTnT-I-C (77 kDa) and cTnI-C (40 kDa) complexes, and fragments (27)(28)(29)(30)(31). In contrast, in renal failure, cTnT circulates primarily as fragments (32 ), whereas the circulating form of cTnI in renal failure is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Differences in renal elimination between both cTn, for example accumulation of cTnT fragments (32 ), may explain their differential association with eGFR (15 ). However, other explanations should also be considered.…”
mentioning
confidence: 99%
“…Clinically, increased hs-cTnT is observed in many asymptomatic renal insufficiency patients with normal ECGs 9,10 , which may be related to minimal myocardial injury and a decreased estimated glomerular filtration rate (eGFR) 11 .Study found that cTnT forms in ESRD patients are small (<18 kDa) and different from forms seen in AMI patients 12 , however, the current test can not distinguish them. Because this test is also affected by renal function, however, it cannot be an effective marker to measure the degree of myocardial injury.…”
Section: Introductionmentioning
confidence: 61%
“…However, studies on both older assays and hs-cTn assays have shown that almost all circulating cTnT molecules in patients with ESRD are degraded into smaller fragments (<20 kDa), small enough for glomerular filtration (102)(103)(104). Recent findings indicate that only intact cTnT and larger primary fragments demonstrate hs-cTnT assay immunoreactivity in patients with MI, which differs from a pattern of immunoreactive small cTnT fragments found in patients with ESRD (103). These observations suggest a principal extrarenal clearance mechanism, conceivably by scavenger receptor-mediated endocytosis in the mononuclear phagocyte system, at high cTnT concentrations e.g.…”
Section: Chronic Myocardial Injury and Renal Functionmentioning
confidence: 99%